2018
DOI: 10.3389/fneur.2018.00102
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up Analysis of Serum TNF-Related Apoptosis-Inducing Ligand Protein and mRNA Expression in Peripheral Blood Mononuclear Cells from Patients with Ischemic Stroke

Abstract: Tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL), which is TNF receptor superfamily member, contributes to several diseases pathogenesis. The aim of this research was to investigate the relevance of serum TRAIL protein levels and mRNA expression in peripheral blood mononuclear cells (PBMC) of patients with stroke through 6 months follow-up. We enrolled patients with first-ever acute ischemic stroke (n = 95) and healthy controls (n = 95) in this study. Follow-up blood samples were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Serum TRAIL protein levels were increased, whereas mRNA expressed on peripheral blood mononuclear cells (PBMC) was down‐regulated as the condition progressed. This shows that TRAIL accord with the chronic regulatory processes from transcription to translation and therefore promises to be a valuable biomarker of ICS 62 …”
Section: Trail and Non‐neoplastic Neurological Diseasesmentioning
confidence: 86%
“…Serum TRAIL protein levels were increased, whereas mRNA expressed on peripheral blood mononuclear cells (PBMC) was down‐regulated as the condition progressed. This shows that TRAIL accord with the chronic regulatory processes from transcription to translation and therefore promises to be a valuable biomarker of ICS 62 …”
Section: Trail and Non‐neoplastic Neurological Diseasesmentioning
confidence: 86%
“…Recently, researchers have shown that serum TRAIL (sTRAIL) levels correlated with stroke outcomes that evaluated at first week after stroke onset 21 . Similarly, another study found that low sTRAIL levels was associated with stroke severity in 293 patients seven days after stroke onset 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Down-regulated genes such as AVBD9, and CABP2, activated under selenium de ciency condition. These genes involved in various functions such as chemoattractant for avian immune cell 19 , calcium transporters 12 , chemokine members 20 , premature ovarian failure 21 , storeoperated calcium entry associated regulatory factor 22 , solute carrier protein 11 , TNF-related apoptosis inducing ligand-like protein 23 , thioredoxin domains 24 , calcium binding protein similar to calmodulin 25 .…”
Section: Discussionmentioning
confidence: 99%